INTEGRATING CORPUS LINGUISTICS INTO TEACHING ENGLISH POLYSEMY: AN EXPERIMENTAL STUDY WITH TEFL LEARNERS - Barnoyeva Nilufar Yoqubovna; Yangiyeva Mohinur Asror qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: Polysemy, the phenomenon whereby a single lexical item possesses multiple related meanings, represents one of the most challenging aspects of vocabulary acquisition for learners of Teaching English as a Foreign Language (TEFL). Traditional vocabulary instruction often presents words in isolation and focuses primarily on their most common meanings, limiting learners’ ability to comprehend and use polysemous words accurately in different contexts. Corpus Linguistics offers an innovative solution by providing authentic language data that enables learners to observe how words function across diverse communicative situations. This study investigates the effectiveness of integrating Corpus Linguistics into teaching English polysemy. An experimental design involving university TEFL students was employed to compare corpus-based instruction with traditional vocabulary teaching methods. The findings indicate that learners exposed to corpus-based activities demonstrated significantly higher levels of polysemy awareness, contextual interpretation, and productive vocabulary use. The study highlights the pedagogical value of Corpus Linguistics in facilitating deeper lexical understanding and recommends its integration into EFL vocabulary instruction.